Factors of leadership, competence, and work discipline play a significant role in employee productivity: Study at Sumenep City District Office - Kurdi, Moh.; Abrar, Unsul; Arifin, Miftahol (PT. Riset Press International, 2023)
The purpose of this study was to analyze the influence of leadership, competence, and work discipline on employee work productivity at the Sumenep City Sub-District Office. The study employed a quantitative approach with a causal method. The population consisted of all 26 employees of the Sumenep City Sub-District Office, all of whom were included as research subjects. Data collection was conducted through validated and reliable questionnaires. Data analysis techniques included F-test, t-test, coefficient of determination (R²), and multiple linear regression using SPSS version 20 software. The results of the study indicated that leadership and work discipline significantly and positively influence employee work productivity. Specifically, leadership had a t-value of 1.496, work discipline had a t-value of 2.957, while competence showed a negative influence with a t-value of -2.598. Simultaneously, leadership, competence, and work discipline collectively had a significant influence on work productivity with an F-value of 17.628. The coefficient of determination showed that 70.6% of the variation in work productivity could be explained by these three independent variables. Therefore, to enhance employee work productivity at the Sumenep City Sub-District Office, improvements in leadership and work discipline are crucial. As for competence, adjustments and enhancements that are more relevant to organizational needs are necessary.